DETERMINATION OF WATER HARDNESS BY TITROMETRY - Odilbekov , B.O.; Abdusalomov , L.SH.; Khurramov, S.K. (Educational Research in Universal Sciences, 2023)
This article presents the determination of water hardness by water hardness and titrometry.